A cross-sectional analysis of investigator needs for non-communicable disease research at the University of the West Indies, Mona - Georgia A Williamson; Shelly Rodrigo; Natalie Guthrie-Dixon; Elizabeth Blackman; J Robert Beck; Ian Hambleton; Althea Bailey; Tomlin Paul; Camille C Ragin; Marshall K Tulloch-Reid (Pan American Health Organization, 2021)
Objective. To describe the needs of academic staff conducting non-communicable disease (NCD) research at the University of the West Indies, Mona Campus in Jamaica. Methods. Utilizing a cross-sectional design an online survey was created using the research electronic data capture application (REDCap); it was disseminated via email to 708 academic staff members in the Faculties of Medical Sciences and Science & Technology between September and November 2018. Participants were asked to indicate their level of access to expertise, training and equipment for conducting research. Descriptive analysis was conducted using STATA version 14. Results. Most respondents were women (74.2%), predominantly scientists (33.1%) or specialist physicians (22.6%). Less than 2/3 of respondents reported publishing research findings in peer reviewed journals, with a quarter not disseminating their research findings in any medium. Resources for field research/data collection, epidemiological methods and principles, and data management/data analysis were generally available. However, there was limited access to training, expertise and equipment in emerging techniques for NCD research such as metabolomics, bioinformatics/analysis of large-scale data sets and health economics. Additional challenges included limited access to financing for research, inadequate workspace and poor administrative support for conducting research. Conclusions. There is a need for more local research seed funding, stronger administrative support for researchers, and opportunities for training in cutting edge NCD research techniques. Jamaican researchers could benefit from being part of a regional research centre of excellence with critical research skills and equipment that builds research networks and strengthens the NCD research response.